A phonological and tonal analysis of Samue using Optimality Theory - Ouattara, Virpi (fi=Turun yliopisto|en=University of Turku|, 2015)
The topic of the present doctoral dissertation is the analysis of the phonological and tonal structures of a previously largely undescribed language, namely Samue. It is a Gur language belonging to the Niger-Congo language phulym, which is spoken in Burkina Faso. The data were collected during the fieldwork period in a Sama village; the data include 1800 lexical items, thousands of elicited sentences and 30 oral texts. The data were first transcribed phonetically and then the phonological and tonal analyses were conducted. The results show that the phonological system of Samue with the phoneme inventory and phonological processes has the same characteristics as other related Gur languages, although some particularities were found, such as the voicing and lenition of stop consonants in medial positions. Tonal analysis revealed three level tones, which have both lexical and grammatical functions. A particularity of the tonal system is the regressive Mid tone spreading in the verb phrase. The theoretical framework used in the study is Optimality theory. Optimality theory is rarely used in the analysis of an entire language system, and thus an objective was to see whether the theory was applicable to this type of work. Within the tonal analysis especially, some language specific constraints had to be created, although the basic Optimality Theory principle is the universal nature of the constraints. These constraints define the well-formedness of the language structures and they are differently ranked in different languages. This study gives new insights about typological phenomena in Gur languages. It is also a fundamental starting point for the Samue language in relation to the establishment of an orthography. From the theoretical point of view, the study proves that Optimality theory is largely applicable in the analysis of an entire sound system.

Tämän tutkielman aiheena on vähemmistökieli samuen fonologinen ja tonologinen analyysi. Samue on laajalti aiemmin dokumentoimaton nigeriläis-kongolaisiin kieliin kuuluva Gur-kieli, jota puhutaan Burkina Fasossa. Aineisto työhön on kerätty samueta puhuvassa kylässä kenttäjakson aikana; se sisältää 1800 leksikaalista sanaa, tuhansia lauseita sekä 30 vapaasti puhuttua tekstiä. Aineisto transkriboitiin ensin foneettisesti, minkä jälkeen aineistosta tehtiin fonologinen ja tonologinen analyysi. Tutkimus osoitti, että samuen äännejärjestelmä vastaa pääosin muiden Gur-kielten äännejärjestelmiä sekä käytössä olevien foneemien että fonologisten prosessien osalta. Tosin kielikohtaisia ilmiöitä myös esiintyy, kuten klusiilien heikentyminen puolivokaaleiksi sanan keskellä. Toonien osalta tutkimuksessa kävi ilmi, että kielessä esiintyvillä kolmella säveltasolla on sekä leksikaalisia että kieliopillisia funktioita kuten muissakin sukukielissä. Erityispiirteenä samuen toonijärjestelmässä on keskisen toonin leviäminen regressiivisesti verbilausekkeissa. Teoreettisena viitekehyksenä tutkimuksessa sovellettiin Optimaalisuusteoriaa, jota on hyvin harvoin käytetty yhden kielen koko fonologisen järjestelmän analysointiin. Yhtenä tutkimuksen tavoitteena olikin selvittää, kuinka hyvin teoria soveltuu koko äännejärjestelmän tutkimukseen. Erityisesti toonien kohdalla tutkimuksessa jouduttiin luomaan kielikohtaisia rajoituksia, vaikka yksi keskeinen Optimaalisuusteorian perusperiaate ovat universaalit rajoitukset, jotka määrittelevät kielen rakenteiden oikeellisuuden ja joita kielissä priorisoidaan eri tavoin. Tutkimus tuo uutta tietoa Gur-kielten typologisista ilmiöistä. Samuen kielen kannalta tutkimus on perustavanlaatuinen, sillä se on yksi lähtökohta kielen tallentamiselle ja kirjoitusasun luomiselle. Teoreettiselta kannalta tutkimus osoittaa, että Optimaalisuusteoria on pääosin sovellettavissa kielen koko äännejärjestelmän analysointiin.